EROSI PANTAI PADA ZONA STABIL SEBAGAI DAMPAK REKLAMASI LOKAL DI PERAIRAN ANYER SELAT SUNDA, BANTEN - Delyuzar Ilhaude (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The studied area is geographically located on the Sunda Strait, Banten Province,  known  as touris  area.  The erosion and sedimentation processes occur along Anyer longshore area.  The mechanism of erosion is strongly caused by the irregular pattern of longshore current and the wave difraction of which they are affected by the breakwater system in the Anyer coast.  The erosion process occurs because of the tidal wave and the maximum height is in the west monsoon in December until februari. Keywords: touristarea, longshore current, erosion coast